Interactions between populations of the calanoid copepod Acartia tonsa Dana and the harpacticoid copepod Tisbe holothuriae Humes in mixed cultures of live feed for fish larvae. (14th December 2017) - Hansen, Benni W; Boesen, Emil; Brodnicke, Ole B; Corfixen, Natasja L; Jepsen, Per M; Larsen, Stephanie M; Læssøe, Casper D; Munch, Pernille S; Nielsen, Peder K F; Olesen, Jørgen; Vismann, Bent; Nilsson, Birgitte
Abstract: Copepods are considered high quality live feed for fish larvae due to their large within species size span, swimming pattern triggering hunting behaviour, and complete biochemical profile. In a continuous cultivation system aiming at the planktonic calanoid Acartia tonsa an intruding harpacticoid frequently appears. We experimentally evaluate how the interaction from the semi‐benthic Tisbe holothuriae is affecting our cultures and ask whether the two copepod‐species are expected to pose competitive exclusion or co‐exist long‐term. This is pursued by establishing ~40 days mono‐ and mixed copepod cultures reared in a stationary setup (S) theoretically advantageous for T. holothuriae and a rotating setup (R) with organisms kept in suspension by use of a plankton wheel, theoretically advantageous for A. tonsa . The carrying capacities of A. tonsa in either mono‐ or mixed cultures are not affected whether the copepods are subject to S or R treatment. Only exception is the S‐setup containing mixed culture were A. tonsa obtains a significantly lower carrying capacity compared with A. tonsa alone in R‐setup. The mono‐ and mixed cultures of T. holothuriae are, however, highly negatively affected by the R setup compared with S setup. A long‐term solution to limit the presence of T. holothuriae is to apply turbulence level in a classical stagnant tank setup to an extend that suppress T. holothuriae and simultaneously allow algae in suspension as food for A. tonsa, make their eggs sediment as well as minimize risk of benthic‐predation on eggs.